Persepsi Pelaku Usaha Kecil dan Menengah terhadap Manfaat Pencatatan Keuangan dalam Menghadapi Ketidakpastian Ekonomi di Medan Utara - Harahap, Taufiq; Aziz, Abdul; Febrina, Devia; Sanjaya, Mega; Chandra, Kuandi (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2025)
This study aims to analyze the perceptions of Micro, Small, and Medium Enterprises (MSMEs) regarding the benefits of financial record-keeping in dealing with economic uncertainty in the North Medan region. A quantitative approach was employed using a survey method involving 100 MSME owners selected through purposive sampling. A structured questionnaire was used to measure perceptions of the functions of financial record-keeping, such as financial control, decision-making, and preparedness for economic risks. Data were analyzed using descriptive statistics and multiple linear regression. The results indicate that positive perceptions of the benefits of financial record-keeping have a significant impact on the readiness of business owners to face economic uncertainty. These findings underscore the importance of enhancing financial literacy among MSMEs as an adaptive strategy in navigating uncertain economic conditions.